Lever-Based Semiactive Inerter and Its Application in Vibration Absorbers. Issue 1 (1st April 2022) - Wu, X C; Cui, K K; Xiong, Y Q; Chen, M Z Q
Abstract: In this paper, a lever structure is proposed to enlarge the range of inertances of existing semiactive inerters. A semiactive inerter with the lever structure would be called lever-based semiactive inerter. The transmission ratio of the lever-based semiactive inerter can be changed by setting a different ratio of the arm of force of the lever, and then the range of inertance of the lever-based semiactive inerter can be enlarged. This paper also presents the mechanical model of the proposed lever-based semiactive inerter. The lever-based semiactive inerter is applied to an adaptive tuned vibration absorber. The frequency-tracker-based control algorithm is derived to maximize vibration reduction of the absorber. It can be shown that the vibration absorber with the lever-based semiactive inerter can adapt to a broader range of frequencies of vibration compared with that of the classical semiactive inerter.